Actitudes hacia el hecho multicultural - Ortega Ruiz, Pedro; Mínguez Vallejos, Ramón (Teoría de la Educación. Revista Interuniversitaria, 2009)
Attitudes towards multiculturalism In this paper, the necessity for a multicultural education responding to the reality of plural society like ours becomes apparent. The conceptual and methodological difficulties surrounding the research into the field of multicultural education are also discussed. Finally, a scale of attitudes towards multiculturalism and a preliminar analysis of the results obtained after the students of the Teachers' Training University School were given the test are presented.